Легенды и мифы Древней Греции - Авдеенко Ольга Ивановна (Школьная библиотека, 2017)
Экземпляры: аб. ДБ (20180730) / Инвентарный номер: 4815 / Цена: / Сис.шифр: 84.2(0) / Авт.знак: Л 38 / ГРНТИ: 17.82 / ББК: 82.3(0)